L'Activité Surréaliste en Belgique : (1924-1950) - Mariën, Marcel (Bruxelles : Editions Lebeer Hossmann, 1979)
Aragon, Louis ; Breton, André ; Chavée, Achille ; Colinet, Paul ; Dotremont, Christian ; Eluard, Paul ; Ernst, Max ; Goemans, Camille ; Magritte, René ; Mesens, E.L.T. ; Nougé, Paul ; etc.
Frans
boek
Keywords: België